Um estudo de áreas com alunos da 6ª série do ensino fundamental - Gomes, Gisela Hernandes (2000)
The purpose of this work was to investigate whether students of the 6th grade could evolve in their knowledge of the area concept during the delivery of a didactic intervention designed in the light of the theoretical framework of Douady. Several previous investigations had already pointed out and tried to explain the difficulties students face during the acquisition of that concept. In the present work, instead of focusing on the difficulties themselves, we sought to analyze the knowledge evolution that students could attain while exposed to a teaching sequence that took into account the phases of the tool object dialectic. In the course of this intervention, phases of the notion of domain interaction where used to keep track of improvements in the students outputs. Assessment of each session enabled us to select topics to be discussed in the subsequent ones, and led to adjustments to the original sequence. Results showed the phases of the tool object dialectic to constitute an effective resource for promoting progress among students in their knowledge of the area concept